La evolución del concepto de talento humano (2018)
This monograph to present below has as purpose to define the concept of the human talent used during several decades, accompanied on the factors that intervene in the concept, emphasizing mainly the management that is given at the business level, highlighting its importance and growth in recent years. This concept has evolved in such a way that currently generates significant value in organizations, creating its own area and training specialists whose objective is to make the worker the most important element of an organization.